19/06/24 12:52:45.29 Iit/WsdM0.net
20/r-tan(b)=22/r-tan(c+d) 変形して
tan(c+d)=22/r-20/r+tan(b)
これと(7)とより
14/r-16/r+tan(a)=22/r-20/r+tan(b) 変形して
tan(a)-tan(b)=22/r-20/r-14/r+16/r=4/r・・・・・・(9)
ここで(2)を変形して
tan(a)+tan(b)=18/rこれと(8)とより
tan(a)=11/r・・・・・・(10)
tan(b)=7/r・・・・・・(11)
これと(11),(8)とより
tan(%pi-b-d)=20/r-7/r=13/r変形して
-(tan(d)+tan(b))/(1-tan(b)*tan(d))=13/r変形して
r*(-tan(d)-tan(b))=13-13*tan(b)*tan(d)
これと(7)とより
r*(-tan(d)-7/r)=13-13*7*tan(d)/r変形して
-r*tan(d)-7=13-13*7*tan(d)/r変形して
-r*tan(d)-20=-13*7*tan(d)/r変形して
-r^2*tan(d)-20*r=-13*7*tan(d)変形して
-20*r=tan(d)*(r^2-91)変形して
tan(d)=-20*r/(r^2-91)・・・・・・(12)